Presenting Symptoms and Predictors of Poor Outcomes Among 2, 184 Patients with COVID-19 in Lagos State, Nigeria. (January 2021) - Abayomi, Akin; Odukoya, Oluwakemi; Osibogun, Akin; Wright, Ololade; Adebayo, Bisola; Balogun, Mobolanle; Abdus-Salam, Ismael; Bowale, Abimbola; Mutiu, Bamidele; Saka, Babatunde; Adejumo, Moyosore; Yenyi, Sam; et al.
Highlights: Cough, fever and difficulty in breathing were the most common COVID-19 symptoms. Severity of symptoms at presentation was the most significant predictor of death. Difficulty in breathing was the most significant symptom predictive of death. The case fatality rate was 4.3%. Abstract: Introduction: Lagos state remains the epicentre of COVID-19 in Nigeria. We describe the symptoms and signs of the first 2, 184 PCR-confirmed COVID-19 patients admitted at COVID-19 treatment centers in Lagos State. We also assessed the relationship between patients' presenting symptoms, sociodemographic and clinical characteristics and COVID-19 deaths.. Methods: Medical records of PCR-confirmed COVID-19 patients were extracted and analyzed for their symptoms, symptom severity, presence of comorbidities and outcome. Results: The ages of the patients ranged from 4 days to 98 years with a mean of 43.0(16.0) years. Of the patients who presented with symptoms, cough (19.3%) was the most common presenting symptom. This was followed by fever (13.7%) and difficulty in breathing, (10.9%). The most significant clinical predictor of death was the severity of symptoms and signs at presentation. Difficulty in breathing was the most significant symptom predictor of COVID-19 death (OR:19.26 95% CI 10.95-33.88). The case fatality rate was 4.3%. Conclusion: Primary care physicians and COVID-19 frontline workers should maintain a high index of suspicion and prioritize the care of patients presenting with these symptoms. Community members should be educated on such predictors and ensure that patients with these symptoms seek care early to reduce the risk of deaths associated with COVID-19.